12 Weeks of Simulated Barefoot Running Changes Foot-Strike Patterns in Female Runners - McCarthy, C.; Fleming, N.; Donne, B.; Blanksby, B. (International Journal of Sports Medicine, 2014)
To investigate the effect of a transition program of simulated barefoot running (SBR) on running kinematics and foot-strike patterns, female recreational athletes (n=9, age 29±3 yrs) without SBR experience gradually increased running distance in Vibram FiveFingers SBR footwear over 12 weeks. Matched controls (n=10, age 30±4 yrs) continued running in standard footwear. A 3-D motion analysis of treadmill running at 12 km/h−1 was performed by both groups, barefoot and shod, pre- and post-intervention. Post-intervention data indicated a more-forefoot strike pattern in the SBR group compared to controls; both running barefoot (P>0.05), and shod (P<0.001). When assessed barefoot, there were significant kinematic differences across time in the SBR group for ankle flexion angle at toe-off (P<0.01). When assessed shod, significant kinematic changes occurred across time, for ankle flexion angles at foot-strike (P<0.001) and toe-off (P<0.01), and for range of motion (ROM) in the absorptive phase of stance (P<0.01). A knee effect was recorded in the SBR group for flexion ROM in the absorptive phase of stance (P<0.05). No significant changes occurred in controls. Therefore, a 12-week transition program in SBR could assist athletes seeking a more-forefoot strike pattern and “barefoot” kinematics, regardless of preferred footwear.
Keywords: biomechanics; minimalist shoes; kinematics; training; transition